2017
DOI: 10.3389/fphys.2017.01045
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation in Age-Related Sarcopenia

Abstract: Many physiological changes occur with aging. These changes often, directly or indirectly, result in a deterioration of the quality of life and even in a shortening of life expectancy. Besides increased levels of reactive oxygen species, DNA damage and cell apoptosis, another important factor affecting the aging process involves a systemic chronic low-grade inflammation. This condition has already been shown to be interrelated with several (sub)clinical conditions, such as insulin resistance, atherosclerosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
356
1
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(375 citation statements)
references
References 221 publications
(235 reference statements)
6
356
1
12
Order By: Relevance
“…Both aerobic and resistance exercise — as well as dietary supplementation of amino acids or protein, vitamin D, and polyunsaturated fatty acids — have been associated with protection against age-associated sarcopenia, possibly because of their antiinflammatory and antioxidative properties 141 . In observational studies, adherence to the Mediterranean diet was the only behavioural factor consistently associated with a lower risk of frailty, which might be a result of the anti-inflammatory properties inherent to the diet 247,248 .…”
Section: Inflammation and Age-related Frailtymentioning
confidence: 99%
“…Both aerobic and resistance exercise — as well as dietary supplementation of amino acids or protein, vitamin D, and polyunsaturated fatty acids — have been associated with protection against age-associated sarcopenia, possibly because of their antiinflammatory and antioxidative properties 141 . In observational studies, adherence to the Mediterranean diet was the only behavioural factor consistently associated with a lower risk of frailty, which might be a result of the anti-inflammatory properties inherent to the diet 247,248 .…”
Section: Inflammation and Age-related Frailtymentioning
confidence: 99%
“…Moreover, we assessed creatine kinase to identify if muscle damage occurred . Vitamin D status, C‐reactive protein (CRP), and interleukin (IL)‐6 and IL‐10 were assessed, because of their possible confounding effects on muscle mass . Glucose, creatinine, urea, albumin, creatine kinase, and CRP were measured using Siemens Dimension Vista 1500 (Siemens Healthcare Diagnostics Inc., Tarrytown, New York, USA).…”
Section: Methodsmentioning
confidence: 99%
“…26 Vitamin D status, C-reactive protein (CRP), and interleukin (IL)-6 and IL-10 were assessed, because of their possible confounding effects on muscle mass. 27,28 Glucose, creatinine, urea, albumin, creatine kinase, and CRP were measured using Siemens Dimension Vista 1500 (Siemens Healthcare Diagnostics Inc., Tarrytown, New York, USA). Serum 25-hydroxyvitamin D concentrations were measured using liquid chromatography coupled to tandem mass spectrometry detection (Waters Chromatography B.V., Etten-Leur, the Netherlands).…”
Section: Blood Samplesmentioning
confidence: 99%
“…Indeed, it has been reported that, even in individuals that are otherwise considered "healthy", skeletal muscle mass has been shown to decrease~1% per year from its peak occurrence between the ages of 20-30 years old [44]. The loss of skeletal muscle mass is multi-factorial and many factors have been identified as contributors to this event; even though this is not an exhaustive list, a few of these factors are anabolic resistance [45][46][47], apoptosis [48,49], chronic inflammatory signaling associated with long-term, low-grade inflammation [50][51][52][53], and neuromuscular alterations such as motor unit loss that leads to skeletal muscle fiber denervation [45][46][47]. This latter event may be the most consequential, given that it could be thought of in terms of an explicit functional event: loss of motor units results in denervation and loss of skeletal muscle fibers, specifically the fastest skeletal muscle fibers, and finally loss of skeletal muscle function [54].…”
Section: Musculoskeletal Disorders (Msds): Dynapenia Sarcopenia Andmentioning
confidence: 99%